2016
DOI: 10.1016/j.neuropharm.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal nicotine exposure disrupts the α2* nicotinic acetylcholine receptor-mediated control of oriens-lacunosum moleculare cells during adolescence in rats

Abstract: Maternal cigarette smoking during pregnancy and maternal nicotine exposure in animal models are associated with cognitive impairments in offspring. However, the underlying mechanism remains unknown. Oriens-lacunosum moleculare (OLM) cells expressing α2* nicotinic acetylcholine receptors (nAChRs) are an important component of hippocampal circuitry, gating information flow and long-term potentiation (LTP) in the CA1 region. Here we investigated whether early postnatal nicotine exposure alters the normal role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…This could represent a significant restructuring of neuronal networks, caused by the persistent presence of nicotine at a time when nicotinic receptors are important modulators of the strength of newly forming excitatory synapses (Maggi et al, 2003; Maggi et al, 2004). Our previous study also showed that early nicotine exposure resulted in facilitated LTP (Nakauchi et al, 2015; Chen et al, 2016). Because LTP is a leading candidate for many forms of memory, we had expected that we would see an association of memory impairments with impaired LTP.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…This could represent a significant restructuring of neuronal networks, caused by the persistent presence of nicotine at a time when nicotinic receptors are important modulators of the strength of newly forming excitatory synapses (Maggi et al, 2003; Maggi et al, 2004). Our previous study also showed that early nicotine exposure resulted in facilitated LTP (Nakauchi et al, 2015; Chen et al, 2016). Because LTP is a leading candidate for many forms of memory, we had expected that we would see an association of memory impairments with impaired LTP.…”
Section: Introductionmentioning
confidence: 71%
“…Additionally, in our rodent models we observed several changes to the way in which nAChR activation modulated CA1 activity and LTP (Nakauchi et al, 2015; Chen et al, 2016). In particular, we found that early postnatal nicotine exposure resulted in the functional loss of α2-containing nAChRs (α2* nAChRs) in oriens-lacunosum moleculare (OLM) cells (Chen et al, 2016), which are located in the stratum oriens and have projections into the stratum lacunosum-moleculare (Freund and Buzsaki, 1996).…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations